A bibliometric study of global trends in diabetic nephropathy and intestinal flora research - Wang, Nuo; Li, Xinyu; Weng, Hanjun; Zhang, Yijun; Li, Qiurui; Luo, Xiaoxiao; Chen, Yu; Dong, Yiyang (Frontiers in Microbiology, 2025)
BackgroundDiabetic nephropathy is chronic kidney damage caused by diabetes and is one of the most common microvascular complications of diabetes. In diabetic patients, prolonged hyperglycemia leads to progressive damage to kidney structure and function. With the increasing incidence of diabetes, the number of patients with Diabetic Nephropathy is also increasing year by year. At present, there is no drug to cure Diabetic Nephropathy. More and more evidence shows that the development of Diabetic Nephropathy is inseparable from the intestinal axis, and the disorder of intestinal flora is related to the progress of diabetes. Maybe we can explore the pathogenesis of Diabetic Nephropathy from the intestinal flora and find new methods to treat Diabetic Nephropathy.MethodsThis article uses CiteSpace VOSviewer and Bibliometrix statistical software explore research hotspots and trends of intestinal flora and Diabetic Nephropathy. The Web of Science Core Collection (WoSCC) was searched for literature from database establishment to December 4, 2024, and ultimately 238 articles were included for quantitative analysis.ResultsThe number of publications has been increasing year by year, reaching its peak in 2024. The high-yield institution is Beijing University of Chinese Medicine, and the most productive country is China. Zhang Yi ranks first in the number of publications by the author. After removing the theme word, inflammation appears the most frequently, followed by oxidative stress. The outbreak hotspots are mainly concentrated in uremic toxin, short chain fatty acid, soy milk, aryl hydrocarbon receptor.ConclusionThe exploration of the mechanism of action and therapeutic or adjuvant therapeutic targets of the gut microbiome and its metabolites in DN patients may become a research hotspot in the future direction of DN and gut microbiome. Inflammation, oxidative stress, and the production of urinary toxins in DN patients are the directions for researchers to explore the mechanisms related to DN patients and gut microbiome. Aryl hydrocarbon receptor (AhR), Short-chain fatty acids (SCFAs), Traditional Chinese medicine and soy milk provide researchers with treatment ideas for diabetic nephropathy. Exploring the specific mechanisms and therapeutic effects of DN and gut microbiome requires cohort studies and clinical trials for validation.